2017
DOI: 10.1186/s40478-017-0454-4
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous ribonuclear protein E2 (hnRNP E2) is associated with TDP-43-immunoreactive neurites in Semantic Dementia but not with other TDP-43 pathological subtypes of Frontotemporal Lobar Degeneration

Abstract: Frontotemporal Lobar Degeneration (FTLD) encompasses certain related neurodegenerative disorders which alter personality and cognition. Heterogeneous ribonuclear proteins (hnRNPs) maintain RNA metabolism and changes in their function may underpin the pathogenesis of FTLD. Immunostaining for hnRNP E2 was performed on sections of frontal and temporal cortex with hippocampus from 80 patients with FTLD, stratified by pathology into FTLD-tau and FTLD-TDP type A, B and C subtypes, and by genetics into patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Mislocalisation of hnRNP K occurs in neurons that are distinct from those which harbour proteinaceous TDP-43 and Tau inclusions that pathologically define FTLD subtypes. This is novel compared to previous work which has identified several other hnRNPs to be present within TDP-43 and FUS inclusions [ 15 , 24 ]. There is also an abundance of research on hnRNPs co-depositing with C9orf72-associated pathologies including RNA foci and dipeptide repeat proteins [ 13 , 14 , 25 , 59 ].…”
Section: Discussionmentioning
confidence: 62%
“…Mislocalisation of hnRNP K occurs in neurons that are distinct from those which harbour proteinaceous TDP-43 and Tau inclusions that pathologically define FTLD subtypes. This is novel compared to previous work which has identified several other hnRNPs to be present within TDP-43 and FUS inclusions [ 15 , 24 ]. There is also an abundance of research on hnRNPs co-depositing with C9orf72-associated pathologies including RNA foci and dipeptide repeat proteins [ 13 , 14 , 25 , 59 ].…”
Section: Discussionmentioning
confidence: 62%
“…By contrast, the pattern of TDP-43 deposition across the FTLD-TDP pathological spectrum is far more heterogeneous with a variety of morphologically distinct cytoplasmic and intranuclear TDP-43 immunoreactive inclusions characterising five molecular sub-types [ 111 ]. HnRNP E2 has been shown to colocalise in FTLD-TDP type C inclusions associated with semantic dementia [ 42 ] and more recently, type A inclusions [ 89 ].…”
Section: Hnrnps and Ftld/als Pathologiesmentioning
confidence: 99%
“…Immunohistochemical studies have confirmed a colocalisation between hnRNP E2 and specific TDP-43 pathologies in FTLD-TDP type C and type A pathologies in postmortem brain tissue [ 42 , 89 ]. Whilst the FTLD-TDP subtype-specificity of hnRNP E2 inclusion remains enigmatic; its potential sequestration within TDP-43 aggregates is further evidence for hnRNP functional deficit within FTLD pathogenesis.…”
Section: The Hnrnp Familymentioning
confidence: 99%
“…It was also found in ALS patients that hnRNP A1, along with TDP-43, had a greater tendency to aggregate in the cytoplasmic inclusions compared to controls [ 150 ]. Another hnRNP, E2, also co-localized with TDP-43 in pathological inclusions of the semantic dementia subtype FTD patients [ 151 ] (Fig. 3 ).…”
Section: Hnrnps In Neurological Diseasesmentioning
confidence: 99%